Jamaica : Eighth Review Under the Arrangement Under the Extended fund Facility and Request for Waiver for the Nonobservance of Performance Criterion and Modification of Performance Criteria. (IMF Staff Country Reports; Country Report ;, 2015)
This paper discusses Jamaica's Eighth Review Under the Arrangement Under the Extended Fund Facility (ECF) and Request for Waiver for the Nonobservance of Performance Criterion (PCs) and Modification of PCs. Jamaica's economic performance under the authorities' economic program is on track and has remained strong. All PCs for end-March 2015 were met, with the exception of the central government primary balance criterion, which was narrowly missed. Structural reforms have advanced broadly in line with the program. The IMF staff supports the authorities' request for completion of the eighth review of the arrangement under the ECF.